Case Report: A case of thyroid storm with lower FT3 and FT4 levels accompanied by acute liver failure - Li, Dezhao; Li, Feifei (Frontiers in Medicine, 2025)
IntroductionThyroid storm and acute liver failure (ALF) each independently carry high mortality rates. Previous literature has rarely reported cases of thyroid storm complicated by ALF, particularly in patients with low thyroid hormone levels.Patient concernsA 34-year-old woman was admitted to our hospital with fever and jaundice. The patient had been taking methimazole for four months following the diagnosis of hyperthyroidism. Upon admission, Laboratory tests revealed elevated liver enzymes and bilirubin levels. Then, she received liver-protective therapy along with medications to reduce liver enzymes and bilirubin, and antithyroid drugs were temporarily discontinued. Unfortunately, the patient subsequently developed thyroid storm and acute liver failure.DiagnosisThe patient was diagnosed with thyroid storm associated with acute liver failure.InterventionsThe patient remarkably improved with plasma exchange and corticosteroids treatment and radioactive iodine therapy was performed two months later.OutcomeThe patient was regularly followed up after discharge and remained clinically stable.LessonsThis case highlights the importance of closely monitoring liver function in patients with hyperthyroidism. In the event of thyroid storm or fulminant liver failure, the use of potentially life-saving interventions such as plasma exchange and corticosteroids should not be delayed.